ION MICROPROBE U-PB DATING OF A DINOSAUR TOOTH - Sano Y.; Terada K.; Ly C.V.; Park E.J. (My University, 2006)
Ion microprobe U-Pb dating of apatite is applied to a fossil tooth of a Allosaurid derived from the Hasandong Formation in the Gyeongsang basin, southeastern Korea. Twelve spots on a single fragment of the fossil dentine yield a TeraWasserburg concordia intercept age of 115 ± 10 Ma (2σ, MSWD = 0.59) on a 238U/206Pb-207Pb/206Pb- 204Pb/206Pb diagram. The age provides a constraint on the depositional age of the fossil in its host Hasandong Formation as Early Aptian. The success of the ion microprobe dating depends on the heterogeneities of diagenetically incorporated U and Pb at the few hundred μm scale, the consequent variations in Pb isotopic compositions due to radioactive decay and the closed-system behavior of U and Pb. There are at least three end-members to explain the variations of minor chemical components such as FeO, SiO2 and Al2O3, and trace elements such as Th, U and rare earth elements (REE) in the sample by a simple mixing model. They are (1) very low minor and REE, very high common Pb with variable U abundances, (2) low common Pb, high minor, REE, and U abundances, and (3) low minor, common Pb, and U with intermediate REE abundances, even though groups (2) and (3) may consist of a larger group. Various contributions of the three (and/or two) end-members during diagenetic prosesses may cause the elemental fractionation of U and Pb in a fossil tooth. Copyright © 2006 by The Geochemical Society of Japan.
Keywords: DIAGENETIC PROCESS; DINOSAUR; FOSSIL TOOTH; RARE EARTH ELEMENTS; U-PB DATING; Aptian; Mesozoic::Cretaceous::Lower::Aptian; Мезозой::Меловая::Нижний::Аптский